An Outlook on Tar Abatement, Carbon Capture and its Utilization for a Clean Gasification Process - Umar, H.A. (Joint Journal of Novel Carbon Resource Sciences and Green Asia Strategy, 2021)
The generation of syngas via gasification is accompanied by greenhouse gas emissions and certain impurities like tar. This is the major problem that makes the technology unattractive for commercialisation. Tar content present in the syngas limits its application as it causes damage to engines, while the CO2that accompanies it adds to the climate issues when released to the atmosphere. In this short review, an overview of techniques used for tar abatement, CO2capturing, and potential areas of CO2utilisation were discussed. Â© 2021 Novel Carbon Resource Sciences. All rights reserved.